Fenomena Pluralisme dan Toleransi Beragama Di Indonesia dalam Perspektif Kekristenan - Cristian Siregar (ILMU USHULUDDIN, 2017)
Wishfull coexistent among religious is an ideal condition in a plural society, such as in Indonesia. To create the ideal conditions of society it requires serious efforts to build pluralism and tolerance among religious communities in Indonesia. One important contribution is the role of Christianity as one of the official religions in Indonesia. This paper describes the phenomenon of pluralism and tolerance that develops in Indonesia today from the perspective of Christianity, especially the Bible. The aim is to provide alternative solutions to the problem of intolerance that often happens in Indonesia recently.